2022
DOI: 10.1039/d2ra02497g
|View full text |Cite
|
Sign up to set email alerts
|

Effects of axial pressure on the evolution of core–shell heterogeneous structures and magnetic properties of Fe–Si soft magnetic powder cores during hot-press sintering

Abstract: Silicon dioxide (SiO2) has attracted much attention as an ideal coating material for iron (Fe)-based soft magnetic powder cores (SMPCs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…P hyst values increased almost linearly with the frequency for all the Fe-Si-Cr-based SMCs. The excessive thickness of the insulating layers restricted the motion of the domain walls, resulting in a gradual increase in the hysteresis loss with an increase in the SS mass fraction [24]. Moreover, the core-shell heterogeneous structure of Fe-Si-Cr-based SMCs primarily reduced the dynamic loss by improving resistivity and restricting the effective operating diameter of the eddy currents [25].…”
Section: Microstructures and Magnetic Properties Of The Alloy Powders...mentioning
confidence: 99%
“…P hyst values increased almost linearly with the frequency for all the Fe-Si-Cr-based SMCs. The excessive thickness of the insulating layers restricted the motion of the domain walls, resulting in a gradual increase in the hysteresis loss with an increase in the SS mass fraction [24]. Moreover, the core-shell heterogeneous structure of Fe-Si-Cr-based SMCs primarily reduced the dynamic loss by improving resistivity and restricting the effective operating diameter of the eddy currents [25].…”
Section: Microstructures and Magnetic Properties Of The Alloy Powders...mentioning
confidence: 99%
“…As a consequence, the resistivity is increased because the Fe-Si particles are prevented from interacting. Another explanation for this is SiO 2 and Fe-Si particles were exchange-coupled, resulting in an efficient surface spin orientation [25]. Nevertheless, after heat treatment at higher temperatures, the permeability of the Fe-Si/SiO 2 SMCs stabilizes at higher frequencies because a complete insulating layer favors an increase in the depth of the skin effect as the working frequency rises [26].…”
Section: Evolution Of the Core-shell Heterostructure Within The Fe-si...mentioning
confidence: 99%
“…Choi et al [17] prepared Al 2 O 3 insulating layers of varying thicknesses on the surface of Fe-Si-Cr alloy powders using the sol-gel method, thereby fabricating a composite with an effective permeability of 33.9 and a loss of 252 mW/cm 3 at 50 mT and 100 kHz. Although previous studies [18][19][20][21] have demonstrated that metal oxides are promising candidates for use as insulating layers in the production of Fe-based SMCs, recent studies have predominantly focused on developing new metal oxide insulating layers and improving the properties of Fe-based SMCs [22,23].…”
Section: Introductionmentioning
confidence: 99%